High-conductivity flexible compressible carbon nano interlayer and preparation method and application thereof
Preparation of high-conductivity flexible compressible carbon nanointerlayers through 3D printing technology solves the problem of deterioration in cycle performance and low capacity caused by low sulfur conductivity and volume changes in lithium-sulfur batteries, and achieves performance improvement in lithium-sulfur batteries .
Patent Information
- Application Number
- CN202411695092.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-02-14
AI Technical Summary
Due to the low conductivity of sulfur, shuttle effect and volume changes, lithium-sulfur batteries have deteriorated circulation performance and low capacity, which hindered their commercial application.
3D printing technology is used to prepare highly conductive flexible compressible carbon nanointerlayers. By mixing carboxylated single-wall carbon nanotubes and cellulose into a precursor ink, cross-linking to build a composite structure, and through directional freezing and annealing treatment, it forms a high specific surface area. and carbon nanointerlayers with high porosity.
This carbon nano-sandwich device effectively alleviates the impact of shuttle effect and volume expansion on battery performance in lithium-sulfur batteries, improves cycling performance and capacity, and has good commercial application prospects.
Smart Images

Figure CN119447713A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium-sulfur batteries, and in particular to a highly conductive, flexible, compressible carbon nano-interlayer and a preparation method and application thereof. Background Art
[0002] Lithium-sulfur batteries are recognized as one of the most promising advanced energy storage systems due to their advantages such as high energy density, high specific capacity and low-cost active materials. However, the high electrochemical energy barrier, shuttle effect, low conductivity of sulfur and volume change of sulfur cathode in Li-S batteries (LiPSs) pose great challenges to the commercialization of lithium-sulfur batteries.
[0003] Additive manufacturing (also known as 3D printing) technology is able to manufacture 3D hierarchical micro / nano structures by depositing layer after layer of precursor materials and solvent-based inks with the help of computer-aided design (CAD) files. It does not require traditional machining and complex mold design, and the external structure and internal structure of the object can be precisely controlled by computer, which greatly reduces production costs and improves production efficiency. Among all 3D printing technologies, direct ink writing technology (DIW) is the most versatile method for manufacturing three-dimensional prototypes. DIW is a layer-by-layer 3D printing technology that can achieve any specified geometry in a bottom-up manner and can accept a wide range of printable materials. It achieves large capacity by utilizing height direction and increasing loading density, thereby realizing the potential for aggregation in a limited space. Carbon-based materials such as graphene, graphene oxide, and carbon nanotubes are usually used for DIW 3D printing. However, their limited dispersion ability and aggregation tendency largely hinder the configuration of printing inks, resulting in a difficult printing process and limited performance after carbonization. Summary of the invention
[0004] In order to solve the above technical problems, the purpose of the present invention is to provide a highly conductive, flexible, compressible carbon nano-interlayer and a preparation method and application thereof. The carbon nano-interlayer device prepared by this method not only reflects the properties of a flexible, compressible conductive reinforced material, but also has a high specific surface area and high porosity. It can effectively alleviate the problems of poor cycle performance and low capacity caused by the shuttle effect, volume expansion and electrochemical reaction kinetics, and has good application prospects in lithium-sulfur batteries.
[0005] The technical solution of the present invention to solve the above technical problems is as follows: a method for preparing a flexible, highly conductive, compressible carbon nano-layer is provided, which comprises the following steps in sequence: (1) Carboxylated single-walled carbon nanotube powder and cellulose aqueous emulsion are mixed, and then a solvent is added and uniformly dispersed to serve as a 3D printing precursor ink; (2) Using 3D printing direct writing technology, cross-linking is used to construct a composite structure, followed by directionally freezing and freeze drying; (3) Annealing in a protective atmosphere to obtain a flexible, highly conductive, compressible carbon nanolayer.
[0006] Furthermore, the purity of carboxylated single-walled carbon nanotubes is 90%~99%, the diameter is 1~2 nm, the length is 5~30 μm, and the oxygen content is >9wt%.
[0007] Furthermore, in step (1), the cellulose is one of cellulose nanofibers, microfibrillated nanocellulose, bacterial nanocellulose and carboxylated cellulose nanocrystals. The cellulose has a diameter of 4 to 500 nm and a length of 100 to 20,000 nm.
[0008] Furthermore, in step (1), the mass ratio of the carboxylated single-walled carbon nanotube powder to the cellulose aqueous emulsion is 0.1:5-15.
[0009] Furthermore, in step (1), the solvent is water.
[0010] Furthermore, in step (1), the mixture is homogenously dispersed at 10-50° C. and 1000-30000 rpm.
[0011] Furthermore, in step (1), the solid content of the 3D printing precursor ink is 5% to 10%.
[0012] Furthermore, the 3D printing distance parameters are 5~20 mm, the needle tip diameter is 0.1~1 mm, and the number of stacking layers is 1~6 layers.
[0013] Furthermore, in step (2), the composite structure is a woodpile-like structure having a solid frame structure.
[0014] Furthermore, the temperature of directional freezing is -90~-30℃, and the cycle is 1 to 10 times; the temperature of freeze-drying is -90~-30℃, and the time is 6 to 72 hours.
[0015] Furthermore, in step (3), the protective atmosphere is at least one of argon and nitrogen.
[0016] Furthermore, in step (3), the temperature is raised to 700-1100° C. at a rate of 1-10° C. / min and annealed for 1-6 h.
[0017] The present invention also provides a flexible, highly conductive, compressible carbon nano-layer prepared by the method for preparing the flexible, highly conductive, compressible carbon nano-layer.
[0018] The present invention also provides application of the flexible, highly conductive, compressible carbon nano-interlayer in a lithium-sulfur battery.
[0019] The present invention has the following beneficial effects: 1. The method of the present invention uses ultra-high purity carboxylated single-walled carbon nanotubes and cellulose as precursor inks, and adopts 3D printing technology to prepare flexible, highly conductive, compressible carbon nano-sandwiches. In the prepared sandwich device, the carbon nanotube and fiber composite structure is evenly distributed, and the porous structure between the fibers is widely present between the layers. The microscopic surface of the sandwich device is rough, with a surface structure similar to that of common interlayers such as carbon paper, and at the same time exhibits the characteristics of high conductivity. The carbon nano-sandwich device prepared by this method not only reflects the properties of flexible, compressible conductive reinforcing materials, but also has a high specific surface area and high porosity, and has good application prospects in carbon nano-sandwich devices for lithium-sulfur batteries.
[0020] 2. The interlayer of the present invention forms a carbon nanotube composite carbon fiber network with several ion-electron network channels; there are pores between the network channels, which can achieve the adsorption of polysulfide ions in the electrolyte through physical confinement, and have a guiding effect on electrons or metal ions; and enhance the conductivity of the electrode, directly contacting the electrode surface. Applying it to lithium-sulfur batteries can effectively alleviate the effects of the shuttle effect, volume expansion and electrochemical reaction kinetics on the battery cycle performance, thereby improving the defects of lithium-sulfur batteries such as low capacity due to the shuttle effect and electrochemical reaction kinetics, and poor cycle performance due to volume expansion during the oxidation-reduction process of active sulfur.
[0021] 3. The method of the present invention adopts 3D printing technology. By controlling the ratio of 3D printing precursor ink, changing the stacking relationship and number of layers of the 3D printing structure, directional freezing and subsequent annealing conditions, the overall conductivity and surface structure of the printed device can be compositely regulated, so that flexible, highly conductive and compressible carbon nano-interlayers can be prepared simply, conveniently and scalably. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 The three-dimensional modeling diagram of the flexible, highly conductive, compressible carbon nanotubes of Examples 1-4; Figure 2 This is a scanning electron microscope image of the flexible, highly conductive, compressible carbon nano-interlayer of Example 1-4; Figure 3 This is the Fourier transform infrared spectrum of the flexible, highly conductive, compressible carbon nano-interlayer of Example 1-4; Figure 4 This is a graph showing the Raman spectrum test results of the flexible, highly conductive, compressible carbon nano-layers of Examples 1-4; Figure 5 The contact angle test results of the flexible, highly conductive, compressible carbon nano-layers of Examples 1-4 are shown; Figure 6 This is the electrochemical impedance test result diagram of lithium-sulfur battery; Figure 7 This is the cycle-specific capacity curve of lithium-sulfur battery. DETAILED DESCRIPTION
[0023] The principles and features of the present invention are described below, and the examples are only used to explain the present invention and are not used to limit the scope of the present invention. If no specific conditions are specified in the embodiments, they are carried out according to normal conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments is not specified, they are all conventional products that can be purchased commercially.
[0024] Example 1 A flexible, highly conductive, compressible carbon nanotube layer (CNF), the preparation method of which comprises the following steps in sequence: (1) 0.1 g of carboxylated single-walled carbon nanotube powder and 12.5 g of cellulose nanofiber emulsion with a solid content of 0.8% were mixed, and then water was added and homogenized at 26 °C for 2 h to prepare the 3D printing precursor ink with a solid content of 7.5%; (2) The needle diameter is selected as 0.8 mm, the spacing is set to 3 mm, the precursor ink volume is 3 mL, the number of printing layers is 2, the distance parameter is 12 mm, and the robot arm acceleration is set to 8 cm / s 2 , a composite structure is constructed by cross-linking through 3D printing direct writing technology (3D modeling diagram as shown in Figure 1 ), then freeze at -70 °C for 3 cycles, and then freeze-dry for 8 h; (3) The temperature was raised to 800°C at a rate of 5°C / min and annealed for 6 h in an argon atmosphere to obtain a flexible, highly conductive, compressible carbon nanolayer.
[0025] Example 2 A flexible, highly conductive, compressible carbon nanotube sandwich (MFC), the preparation method of which comprises the following steps in sequence: (1) 0.1 g of carboxylated single-walled carbon nanotube powder and 5 g of 2% solid content microfibrillated nanocellulose emulsion were mixed, and then water was added and homogenized at 28 °C for 3 h to prepare the 3D printing precursor ink with a solid content of 6.5%. (2) The needle diameter is 1 mm, the spacing is set to 2.5 mm, the precursor ink volume is 2 mL, the number of printing layers is 4, the distance parameter is 10 mm, and the robot arm acceleration is set to 6 cm / s 2 , a composite structure is constructed by cross-linking through 3D printing direct writing technology (3D modeling diagram as shown in Figure 1 ), followed by -80 °C directional freezing, cycled 5 times, and then freeze-dried for 12 h; (3) The temperature was raised to 1100°C at a rate of 5°C / min and annealed for 3 h in an argon atmosphere to obtain a flexible, highly conductive, compressible carbon nanolayer.
[0026] Example 3 A flexible, highly conductive, compressible carbon nanolayer (BCN), the preparation method of which comprises the following steps in sequence: (1) 0.1 g of carboxylated single-walled carbon nanotube powder and 12.5 g of bacterial nanocellulose emulsion with a solid content of 0.8% were mixed, and then water was added and homogenized at a speed of 20,000 rpm to prepare a 3D printing precursor ink with a solid content of 10%; (2) The needle diameter is selected as 0.2 mm, the spacing is set to 2 mm, the precursor ink volume is 4 mL, the number of printing layers is 3, the distance parameter is 12 mm, and the robot arm acceleration is set to 10 cm / s 2 , a composite structure is constructed by cross-linking through 3D printing direct writing technology (3D modeling diagram as shown in Figure 1 ), followed by -80 °C directional freezing, 10 cycles, and then freeze drying for 72 h; (3) The temperature was raised to 700°C at a rate of 3°C / min in an argon atmosphere and annealed for 1 h to obtain a flexible, highly conductive, compressible carbon nanolayer.
[0027] Example 4 A flexible, highly conductive, compressible carbon nanotube sandwich (C-CNC), the preparation method of which comprises the following steps in sequence: (1) 0.1 g of carboxylated single-walled carbon nanotube powder and 12.82 g of 7.8% solid content carboxylated cellulose nanocrystal emulsion were mixed, and then water was added and homogenized at 26 °C for 2 h to prepare the 3D printing precursor ink with a solid content of 10%. (2) The needle diameter is selected as 0.6 mm, the spacing is set to 2 mm, the precursor ink volume is 6 mL, the number of printing layers is 6, the distance parameter is 13 mm, and the robot arm acceleration is set to 12 cm / s 2 , a composite structure is constructed by cross-linking through 3D printing direct writing technology (3D modeling diagram as shown in Figure 1 ), followed by -90 °C directional freezing, six cycles, and then freeze drying for 6 h; (3) The temperature was raised to 900 °C at a rate of 10 °C / min and annealed for 2 h in an argon atmosphere to obtain a flexible, highly conductive, compressible carbon nanolayer.
[0028] Example 5 A flexible, highly conductive, compressible carbon nano-layer, the preparation method of which comprises the following steps in sequence: (1) 0.1 g of carboxylated single-walled carbon nanotube powder and 15 g of cellulose nanofiber emulsion with a solid content of 0.8% were mixed, and then water was added and homogenized to obtain a 3D printing precursor ink with a solid content of 5%; (2) The needle diameter is 0.6 mm, the spacing is set to 3 mm, the amount of precursor ink is 3 mL, the number of printing layers is 2, the distance parameter is 10 mm, and the robot arm acceleration is set to 6 cm / s 2 The composite structure was cross-linked and constructed by 3D printing direct writing technology, and then directionally frozen at -30℃, cycled once, and then freeze-dried for 24 h; (3) The temperature was raised to 700 °C at a rate of 1 °C / min in a nitrogen atmosphere and annealed for 3 h to obtain a flexible, highly conductive, compressible carbon nanolayer.
[0029] Test Example 1 (1) Scanning electron microscopy images of flexible, highly conductive, compressible carbon nanostructured layers of Example 1-4 are shown in Figure 2 shown.
[0030] Depend on Figure 2 It can be seen that the microscopic morphology of the flexible, highly conductive, compressible carbon nano-interlayers of Examples 1-4 are all network structures composed of carbon nanotubes and carbon nanofibers. The holes in the network structure are widely distributed without obvious accumulation. The surface of the carbon nanotubes and fibers is rough, similar to the surface structure of common interlayers such as carbon cloth, which can prevent the shuttling of polysulfides at the physical confinement level.
[0031] (2) The Fourier transform infrared spectrum of the flexible, highly conductive, compressible carbon nanostructured layer of Example 1-4 is shown in Figure 3 shown.
[0032] Depend on Figure 3 It can be seen that the spectra of the flexible, highly conductive, compressible carbon nanolayers of Examples 1-4 all show the properties of carbon-based materials, containing carbon-carbon double bonds and carbon-oxygen double bonds functional groups, and the presence of polar groups can effectively capture polysulfides during the electrochemical reaction and kinetically promote electrochemical behavior.
[0033] (3) The Raman spectrum test results of the flexible, highly conductive, compressible carbon nanostructured interlayers of Examples 1-4 are as follows: Figure 4 As shown, A is the Raman spectrum, and B is the intensity ratio of the D peak and the G peak.
[0034] Depend on Figure 4It can be seen that the Raman spectrum test results of the flexible, highly conductive, compressible carbon nano-interlayers of Examples 1-4 show that there are a large number of defects in the carbon body, and these defects can provide more active sites during the redox reaction. The intensity ratio of the D band and the G band (ID / IG) can be used to judge the degree of defects in the carbon material. The larger the ID / IG, the more defects there are in the carbon material. After calculation, the ID / IG values of TCNF, MFC, C-CNC and BCN are 1.02283, 0.65165, 0.47849 and 0.06148, respectively. Among them, the ID / IG value of BCN is the largest, and the defect and disorder degree of the carbon composite material, that is, the ratio of the D peak to the G peak, shows that the defects of the four groups of samples of BCN, C-CNC, MFC and TCNF decrease in turn.
[0035] (4) The contact angle test results of the flexible, highly conductive, compressible carbon nanostructured interlayer of Example 1-4 are as follows: Figure 5 shown.
[0036] Depend on Figure 5 It can be seen that the flexible, highly conductive, compressible carbon nanolayers of Examples 1-4 can complete wetting at the moment of contact with the lithium-sulfur battery electrolyte (ethylene glycol dimethyl ether and 1,3-dioxolane in a volume ratio of 1:1), and the time for the four groups of samples of TCNF, MFC, BCN and C-CNC is 300 ms, 500 ms, 300 ms and 600 ms, respectively.
[0037] Test Example 2 The active material sulfur and the conductive carbon nanotubes MWCNT were mixed in a mass ratio of 3:1 to prepare an S / C mixture. 0.45 g of the mixture was melted at 155°C for 24 h, and then mixed with LA133 in a mass ratio of 9:1. 1.3 g of deionized water was added dropwise, and the mixture was stirred in a degassing machine for 1 h to obtain a positive electrode slurry. The positive electrode slurry was coated on the surface of an aluminum foil to form a 250 μm thick wet film, which was then vacuum dried and cut into positive electrode sheets with a diameter of 13 mm using a cutting machine.
[0038] The flexible, highly conductive, compressible carbon nano-interlayers of Examples 1-4 were used respectively, and the lithium-sulfur battery was assembled in the order of positive electrode, interlayer, diaphragm, lithium sheet, gasket and shrapnel in an argon-protected and dry MIKROUNA glove box. Among them, the battery accessories are 2032 button batteries, the diaphragm is Celgrad 2500, and the electrolyte used for battery assembly is a lithium-sulfur electrolyte in which 1M lithium bistrifluoromethylsulfonimide (LiTFSI) containing 2wt% LiNO3 is dissolved in a mixture of ethylene glycol dimethyl ether and 1,3-dioxolane in a volume ratio of 1:1. At the same time, a lithium-sulfur battery without adding an interlayer was assembled as a comparison.
[0039] (1) Electrochemical impedance spectroscopy was performed on the assembled lithium-sulfur battery. Figure 6shown.
[0040] Depend on Figure 6 It can be seen that the addition of the interlayer reduces the overall interface charge transfer resistance, and the ion transfer rate is also significantly improved, indicating that the addition of the interlayer can effectively improve the internal ion and electron transport of lithium-sulfur batteries, among which the TCNF group is the most obvious, and the interface impedance RCT is directly reduced from 122 to 20.
[0041] (2) The assembled lithium-sulfur battery was cycled at a current density of 0.2 C. The cycle-specific capacity curve is shown in Figure 7 shown.
[0042] Depend on Figure 7 It can be seen that the addition of the interlayer significantly improves the overall effective specific capacity and the capacity retention rate. Among them, the TCNF and MFC groups perform best, each of which can maintain about 1200 mAh∙g -1 and 1100mAh∙g -1 Specific capacity.
[0043] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modification, equivalent substitution or improvement made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a flexible, highly conductive, compressible carbon nano-layer, characterized in that: The following steps are included in sequence: (1) Carboxylated single-walled carbon nanotube powder and cellulose aqueous emulsion are mixed, and then a solvent is added and uniformly dispersed to serve as a 3D printing precursor ink; (2) Using 3D printing direct writing technology, cross-linking is used to construct a composite structure, followed by directional freezing and freeze drying; (3) Annealing in a protective atmosphere to obtain a flexible, highly conductive, compressible carbon nanolayer.
2. The method for preparing the flexible, highly conductive, compressible carbon nano-layer according to claim 1, characterized in that: In step (1), the cellulose is one of cellulose nanofibers, microfibrillated nanocellulose, bacterial nanocellulose and carboxylated cellulose nanocrystals.
3. The method for preparing the flexible, highly conductive, compressible carbon nano-layer according to claim 1, characterized in that: In step (1), the mass ratio of the carboxylated single-walled carbon nanotube powder to the cellulose aqueous emulsion is 0.1:5-15.
4. The method for preparing the flexible, highly conductive, compressible carbon nano-layer according to claim 1, characterized in that: In step (1), the solvent is water.
5. The method for preparing the flexible, highly conductive, compressible carbon nano-layer according to claim 1, characterized in that: In step (1), the solid content of the 3D printing precursor ink is 5% to 10%.
6. The method for preparing the flexible, highly conductive, compressible carbon nano-layer according to claim 1, characterized in that: In step (2), the composite structure is a woodpile-like structure.
7. The method for preparing the flexible, highly conductive, compressible carbon nano-layer according to claim 1, characterized in that: In step (3), the protective atmosphere is at least one of argon and nitrogen.
8. The method for preparing the flexible, highly conductive, compressible carbon nano-layer according to claim 1, characterized in that: In step (3), the temperature is raised to 700-1100°C at a rate of 1-10°C / min and annealed for 1-6 h.
9. A flexible, highly conductive, compressible carbon nano-interlayer prepared by the method for preparing a flexible, highly conductive, compressible carbon nano-interlayer according to any one of claims 1 to 8.
10. Use of the flexible, highly conductive, compressible carbon nano-interlayer according to claim 9 in lithium-sulfur batteries.